2019
DOI: 10.1259/bjr.20190240
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the participation rate between CT colonography and colonoscopy in screening population: a systematic review and meta-analysis of randomized controlled trials

Abstract: Objective: To compare the participation rate between CT colonography (CTC) and colonoscopy in screening population in randomized controlled trials (RCTs). Methods: A search was performed using the PubMed, Web of Science, and Cochrane databases. RCTs that included screening populations and reported participation number were assessed. Cochrane risk of bias tool was used to assess the bias and quality. Risk ratio (RR) was used to present the results. The non-participation rate was analyzed to verify the results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…In our study, we achieved an overall good participation rate (56.5%), with better engagement of women (63.4%) and of the 50-60 age group for both sexes (38% of all participants). These results indicate an improvement from the previously published data, where the overall participation rate of CTC screening was 25% [ 18 , 23 ]. It should be noted, however, that participants’ sociodemographic and health status characteristics, as well as bowel preparation techniques in these referenced trials, are different from ours.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In our study, we achieved an overall good participation rate (56.5%), with better engagement of women (63.4%) and of the 50-60 age group for both sexes (38% of all participants). These results indicate an improvement from the previously published data, where the overall participation rate of CTC screening was 25% [ 18 , 23 ]. It should be noted, however, that participants’ sociodemographic and health status characteristics, as well as bowel preparation techniques in these referenced trials, are different from ours.…”
Section: Discussionsupporting
confidence: 58%
“…These results indicate an improvement from the previously published data, where the overall participation rate of CTC screening was 25%. 18,23 It should be noted, however, that participants' sociodemographic and health status characteristics, as well as bowel preparation techniques in these referenced trials, are different from ours.…”
Section: Discussionmentioning
confidence: 61%
“…Zhu et al showed that CTC had a higher patient participation rate than OC, although the difference was not statistically significant [54]. The rate of non-participation, on the other hand, was statistically significant.…”
Section: Patient Acceptability Practicability and Safety Concernsmentioning
confidence: 96%
“…The screening population appeared to be more likely to participate in the CTC with minimal or no cathartic preparation [54]. According to statistical evidence, more large randomized controlled trials (RCTs) will be required in the future [54].…”
Section: Patient Acceptability Practicability and Safety Concernsmentioning
confidence: 99%
See 1 more Smart Citation